Modern pandemics: Recession and recovery - Chang Ma; John H. Rogers; Sili Zhou (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
We examine the immediate effects and bounce-back from six modern health crises: 1968 Flu, SARS (2003), H1N1 (2009), MERS (2012), Ebola (2014), and Zika (2016). Time-series models for a large cross-section of countries indicate that real GDP growth falls by around three percentage points in affected countries relative to unaffected countries in the year of the outbreak. Bounce-back in GDP growth is rapid, but output is still below pre-shock level five years later. Unemployment for less educated workers is higher and exhibits more persistence, and there is significantly greater persistence in female unemployment than male. The negative effects on GDP and unemployment are felt less in countries with larger first-year responses in government spending, especially on health care. Affected countries' consumption declines, investment drops sharply, and international trade plummets. Bounce-back in these expenditure categories is also rapid but not by enough to restore pre-shock trends. Furthermore, indirect effects on own-country GDP from affected trading partners are significant for both the initial GDP decline and the positive bounce back. We discuss why our estimates are a lower bound for the global economic effects of COVID-19 and compare contours of the current pandemic to the historical episodes.
URN:NBN:fi:bof-202007032221
Keywords: I10; E60; F40; 330; Health crises; COVID-19; Output loss; Unemployment; Trade network; Fiscal policy